Carcinogenic and Non-Carcinogenic Health Risk Assessment of Heavy Metals in Noyyal River Basin, Tamil Nadu, India - Madhumitha, R.; Kumaraswamy, K. (Department of Geography Education, University of Jember, Indonesia, 2025)
The extensive agriculture, industrial, and resultant urbanization have led to contamination of groundwater resources of the Noyyal river basin. This study aims to evaluate the spatial variability of human exposure risk to heavy metals, particularly in the context of geographic applications for health. The groundwater samples were collected from the 48 locations of the basin. Its heavy metal concentrations of chromium (Cr), manganese (Mn), iron (Fe), nickel (Ni), copper (Cu), zinc (Zn), lead (Pb), and cadmium (Cd) were analyzed with Inductively Coupled Plasma Mass Spectrometer (ICP-MS). Human exposure to heavy metals was evaluated using the United States Environmental Protection Agency (US EPA) standard health risk assessment guidelines. Here, the health risk assessment is carried out for adults and children via drinking and dermal exposures of the contaminated groundwater. The non-carcinogenic risk assessment results show that the HQing for the individual heavy metals of Fe, Pb, and Ni exceeds the safe level (>1) while HQdermis under the safe level for all the heavy metals. The total hazard quotient (HQing + HQderm) is higher for children than adults. The carcinogenic risk assessment reveals that cadmium and nickel pose a high cancer risk over adults and children through the oral pathway, whereas chromium and cadmium have a carcinogenic effect on adults through the dermal pathway. The result obtained indicates that children are identified as more prone to health risks through oral ingestion of contaminated groundwater, and special attention is needed to overcome the health issues.